Social Media Engagament sebagai sarana Literasi Hybrid Banking Syariah Pada Generasi Milenial - Ulya Unsta Stania; Hajar Mukaromah; M. Nurul Fahmi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze social media engagement as a means of Islamic hybrid banking literacy among the millennial generation. The background of this study is based on the rapid digitalization of Islamic banking which encourages the implementation of the hybrid banking model as an integration of digital and physical services. Although the millennial generation is known as a group that actively uses social media, the level of literacy regarding the concept and mechanisms of Islamic hybrid banking is still relatively limited, especially regarding the understanding of Islamic principles. This study uses a descriptive qualitative approach with field research methods. Data collection was carried out through in-depth interviews, observation of social media activities, and documentation. Data analysis uses the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results show that social media engagement plays a role as a means of Islamic hybrid banking literacy through cognitive, affective, and behavioral dimensions. The active involvement of the millennial generation in social media can increase knowledge, positive attitudes, and skills in understanding and using Islamic hybrid banking services. However, the use of interactive social media features is still more oriented towards promotion than in-depth education. This research is expected to be an evaluation material in developing a digital communication strategy based on Islamic banking literacy.